2008
DOI: 10.1007/s12011-007-8062-y
|View full text |Cite
|
Sign up to set email alerts
|

Copper, Chromium, Manganese, Iron, Nickel, and Zinc Levels in Biological Samples of Diabetes Mellitus Patients

Abstract: There is accumulating evidence that the metabolism of several trace elements is altered in diabetes mellitus and that these nutrients might have specific roles in the pathogenesis and progress of this disease. The aim of present study was to compare the level of essential trace elements, chromium (Cr), copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), and zinc (Zn) in biological samples (whole blood, urine, and scalp hair) of patients who have diabetes mellitus type 2 (n = 257), with those of nondiabetic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
257
4
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(314 citation statements)
references
References 46 publications
38
257
4
15
Order By: Relevance
“…Low circulating zinc (in plasma or white blood cells) is common among hospitalized elderly patients and has been associated with many diseases including DM and AD (Walter et al 1991;Prasad et al 1993;Singh et al 1998;Pepersack et al 2001;Kazi et al 2008;Brewer et al 2010). However, in some cases (e.g.…”
Section: Risk Of Zinc Deficiency In the Elderlymentioning
confidence: 99%
“…Low circulating zinc (in plasma or white blood cells) is common among hospitalized elderly patients and has been associated with many diseases including DM and AD (Walter et al 1991;Prasad et al 1993;Singh et al 1998;Pepersack et al 2001;Kazi et al 2008;Brewer et al 2010). However, in some cases (e.g.…”
Section: Risk Of Zinc Deficiency In the Elderlymentioning
confidence: 99%
“…The studies that compared the levels of essential trace elements in biological samples of patients who have diabetes mellitus type 2, with those of nondiabetic control subjects, have suggested that deficiency and accumulation of some essential trace metals may play a role in the development of diabetes mellitus. 26,27 However, some toxic metals have been analyzed that the mean concentrations of these heavy metals were significantly higher in scalp hair samples of smoker and non-smoker diabetic patients as compared to control subjects, suggesting that toxic metals may play a role in the development of diabetes mellitus. 28 In the present work, we review the important roles of heavy metals in islet function and diabetes development in which the in vitro, in vivo or human evidences are associated with exposure to zinc, arsenic, cadmium, mercury and nickel.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium concentrations were significantly reduced in blood of T2DM patients as compared to control subjects of both genders but urinary levels of these elements were found to be higher in the diabetic patients than in the age-matched healthy controls [6].…”
mentioning
confidence: 78%